Should Remaining Stockpiles of Smallpox Virus (Variola) Be Destroyed? - Raymond S. Weinstein (Emerging Infectious Diseases, 2011)
In 2011, the World Health Organization will recommend the fate of existing smallpox stockpiles, but circumstances have changed since the complete destruction of these cultures was first proposed. Recent studies suggest that variola and its experimental surrogate, vaccinia, have a remarkable ability to modify the human immune response through complex mechanisms that scientists are only just beginning to unravel. Further study that might require intact virus is essential. Moreover, modern science now has the capability to recreate smallpox or a smallpox-like organism in the laboratory in addition to the risk of nature re-creating it as it did once before. These factors strongly suggest that relegating smallpox to the autoclave of extinction would be ill advised.